ФЕМИНАТИВЫ С СУФФИКСОМ -К(А) В НОВОЙ РУССКОЙ ЛЕКСИКЕ - НОВИЦКА, БЕАТА (Studia Rossica Posnaniensia, 2006)
The author attempts to examine the newest Russian feminatives with the suffix -к(а). The feminatives have been categorized on the basis of formal and derivational structure of their motivating words. The widespread phenomenon of synonymy between the feminatives with the suffix -к(а) and other suffixes have also been presented.